Autologous Descemet Stripping Automated Endothelial Keratoplasty to Eliminate Endothelial Rejection in Eyes at High Risk. Issue 5 (May 2020) - Myerscough, James; Friehmann, Asaf; Bovone, Cristina; Busin, Massimo
Abstract : Purpose: To determine whether autologous Descemet stripping endothelial keratoplasty is technically feasible and whether it eliminates the risk of endothelial rejection in "only eyes" at high risk of immunological rejection. Methods: This is a prospective observational interventional study from 2016 to 2018 with a 24-month follow-up in a tertiary-level corneal referral center, Forlì, Italy. One 25-year-old woman with failed penetrating keratoplasty after endothelial rejection in the context of chronic panuveitis and a blind fellow eye due to retinal detachment underwent autologous Descemet stripping automated keratoplasty. An endothelial graft was harvested from the fellow eye by performing a hinged, microkeratome-assisted superficial stromal flap, with removal of the central posterior stromal bed. The posterior lamellar graft created was then transplanted into the other eye using a standardized Descemet stripping automated endothelial keratoplasty (DSAEK) technique. Main outcome measures were endothelial rejection, best spectacle-corrected visual acuity, and endothelial cell density. Results: No endothelial rejection was seen during the 2-year follow-up duration. Stable improvement in best spectacle-corrected visual acuity from 0.2 to 0.4 (decimal Snellen) was observed. Endothelial cell density of 1465 (cells/mm 2 ) was recorded at the final follow-up. Conclusions: The use of this repeatable technique to harvest and transplant an autologous DSAEK graft eliminates endothelial rejection in high-risk eyes. Abstract : Supplemental Digital Content is Available in the Text.